Persepsi Korupsi dan Kondisi Makroekonomi Terhadap Investasi Asing Di Indonesia, Filipina dan Thailand - Regina Niken Wilantari; Gelora Seven Saragih; Fajar Wahyu Prianto (MediaTrend, 2020)
Countries in the ASEAN region largely classified as a developing countries. Economic development in developing countries more slowly or lagging from behind developed countries. To catch up, needed enormous capital flows which can not be fulfilled by the flow of capital of domestic. The flow of foreign capital in the form of FDI can be solution in dealing with the limitations of domestic capital.  FDI can be potential supporting sector in implementing economic development,  besides transferring technologies  and skill.  The entry of FDI  into the country can not be separated from the macroeconomic stability  of  the  country.  The  purpose  of  this  research  was  to  determine  the  effect  of  indicators  of  fundamental Macroeconomics  consisting  of  economic  growth,  interest  rate,  and  exchange  rate  on  FDI  in  five  ASEAN countries (Indonesia,  Singapore,  Malaysia,  Thailand,  and  the  Philippines).  The  research  use  two  analysis  method,  they  are descriptive and quantitative analysis by using Panel  Data Regression method which Fixed Effect  Model  approach. The result of Panel Data Regression which Fixed Effect Model approachshowed that the effect of variables of economic growth and the exchange rate  on positive and significant,  while the effect  of variable interest  rate showed on positive significant.